Simple Assay for Clindamycin in the Presence of Aminoglycosides - Ervin, F. Richard (1974)
The presence of aminoglycoside antibiotics interferes with the determination of clindamycin levels by standard microbiological assay. A new bioassay method of quantitation of clindamycin in the presence of aminoglycosides is presented. This technique is based on the fact that incorporation of calcium chloride into assay agar blocks the antimicrobial activity of aminoglycosides against Sarcina lutea but allows the assay of as little as 0.31 μg of clindamycin per ml. The error of the system is less than 10%. This method is simple and adaptable to existing assay systems for clindamycin.